Strategies To Reduce Needle Stick Injury Incidence Among Medical Personnel In Emergency Room And Central Operating Theatre At Royal Prima Hospital - Kalvin Raveli; Ermi Girsang; Sri Lestari Ramadhani; Chrismis Novalinda Ginting (International Journal of Health and Pharmaceutical (IJHP), 2022)
One of the most frequent occurrences in the Emergency Room and Central Surgical Installation of a hospital is a Needle Stick Injury. The incidence of needle sticks at Royal Prima Medan during 2020-2021 is known that the risk of infection due to needlestick wounds and sharp objects reaches 1.8%, with varying rates of HIV 2.5%, Hepatitis B and C by 40%. This study aims to analyze how the strategy is to reduce needlestick injuries for medical personnel in the emergency department and the central surgical installation of the Royal Prima Hospital. This type of research is qualitative research. The location of this research was carried out in the ER and the Central Surgical Installation of the Royal Prima Hospital. The research informants were the head of the emergency room and the head of the central surgical installation, medical personnel in the emergency room and the central surgical installation, cleaning staff. Data were collected using participatory observation, in-depth interviews, and activity documentation. The results showed that the strategy to reduce injury was to prepare a needle holder or safety box, needles or sharp objects must be put in the safety box that has been provided, what was done so that officers were not stabbed by needles was that every briefing was always reminded so that the officers did the injection according to the procedure. and so that used needles are immediately put into the safety box so that officers do not experience needle sticks, the cause of needle sticks in the room is that the nurse in the room is tired of her work, so there is negligence in doing the injection so that there is an incident of being stabbed with used needles. This study suggests that the results of this study be used as a reference in making policies to prevent work accidents, add officers to reduce workloads, and disseminate information to all employees about the importance of implementing occupational safety and health.